On the Connectedness of Graphic Topology - Amna A. Eldelensi; Hawa A.Alrawayati; Aisha S. Safar (African Journal of Advanced Pure and Applied Sciences, 2025)
In this study, we delve into the intricate aspects of graphic topology. We establish the special cases in which topological spaces have a graphic topology, and relation between the graphic topology and certain graphs, we present connected graphic topology, moreover, show that the graphic topological space is irreducible if and only if the graph is empty. Finally, we offer the of connectivity of graph through special conditions on adjacency sets.